Patient Delay in Breast Cancer Diagnosis in Two Hospitals in Karachi, Pakistan: Preventive and Life-Saving Measures Needed - Shamsi, Uzma (JCO Glob Oncol, 2020)
PURPOSE: Patients with breast cancer in Pakistan commonly present with advanced disease. The objectives of this study were to evaluate the frequency and length of delays in seeking medical consultation and to assess the factors associated with them. METHODS: Four hundred ninety-nine patients with newly diagnosed breast cancer were enrolled and interviewed over the period from February 2015 to August 2017. Information on sociodemographic factors, delay to medical consultation, stage of breast cancer at presentation, and tumor characteristics of the breast cancer were collected through face-to-face interviews and medical file review. RESULTS: The mean (standard deviation) age of patients with breast cancer was 48.0 (12.3) years. The mean (standard deviation) patient delay was 15.7 (25.9) months, with 55.2% of women detecting a breast lump but not seeking a medical consultation because of a lack of awareness about the significance of the lump. A total of 9.4% of the women decided to seek treatment initially using complementary and alternative medicine and traditional treatment; 9.4% of the women presented to a health care provider with a breast lump but no action was taken, and they were wrongly reassured about the lump without mammography or biopsy. For 26% of the women, the delay in presentation was caused by anxiety, fears and misconceptions regarding diagnosis and treatment, and other social factors including possible adverse effects on their relationship with their husband. Multivariable analysis showed a strong association of lower socioeconomic status (odds ratio [OR], 8.11 [95% CI, 2.46 to 26.69]) and late stage of breast cancer (OR, 4.83 [95% CI, 1.74 to 13.39]) with a patient delay of ≥ 3 months. CONCLUSION: Patient delay is a serious problem in Pakistan. There is an urgent need for intensive and comprehensive breast cancer education that addresses the myths and misconceptions related to breast cancer.